2009
DOI: 10.35649/kubr.2008.6.12.1
|View full text |Cite
|
Sign up to set email alerts
|

Occupation Pattern of Waterlogged People: A Study on the South-West Region of Bangladesh

Abstract: Water logging hinders normal life of people and lowers their socioeconomic status. Disruption of regular crop and fish cultivation compels farmers to pursue alternative crops and methods of cultivation to adapt with changes and to shift from their traditional occupations. Push factors are mainly responsible for waterlogged peoples' occupational changes. Unemployment, underemployment, and migration are three important consequences of water logging. Waterlogged people are trying to face these consequences throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…As highlighted in this article, the impacts of excess of NaCl on the populations of bacteria and plants, raises concerns about potential deterioration of water and soil quality due to this pollution. Reports suggested that high salt concentrations could directly reduce microbial diversity and biomass in water and soil (Ruhl et al, 2018; Wichern et al, 2006), potentially leading to severe ecological imbalances (Haider et al, 2009; Weber-Scannell et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As highlighted in this article, the impacts of excess of NaCl on the populations of bacteria and plants, raises concerns about potential deterioration of water and soil quality due to this pollution. Reports suggested that high salt concentrations could directly reduce microbial diversity and biomass in water and soil (Ruhl et al, 2018; Wichern et al, 2006), potentially leading to severe ecological imbalances (Haider et al, 2009; Weber-Scannell et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The resulted water-logging causes serious damage to agriculture, forestry, fisheries, physical infrastructures and thereby impact on livestock [14]. The area suffers from scarcity of pure drinking water, sanitation system and utility services, as well as squeezed educational and recreational facilities.…”
Section: Journal Of Dairy and Veterinary Sciencesmentioning
confidence: 99%
“…Water logging destroys educational and religious institutions, housing conditions and reduces scope for other utility services. Again reduced land productivity, water pollution, deforestation and depletion of species are the direct consequences of water logging in the South-western region of Bangladesh [10]. It is important to note that water logging affects local biodiversity in that region, which subsequently changes the lives and livelihoods of the people of that area.…”
Section: Water Logging Problem In the Study Areamentioning
confidence: 99%